x(x+2)=(x+2)

Simple and best practice solution for x(x+2)=(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x+2)=(x+2) equation:



x(x+2)=(x+2)
We move all terms to the left:
x(x+2)-((x+2))=0
We multiply parentheses
x^2+2x-((x+2))=0
We calculate terms in parentheses: -((x+2)), so:
(x+2)
We get rid of parentheses
x+2
Back to the equation:
-(x+2)
We get rid of parentheses
x^2+2x-x-2=0
We add all the numbers together, and all the variables
x^2+x-2=0
a = 1; b = 1; c = -2;
Δ = b2-4ac
Δ = 12-4·1·(-2)
Δ = 9
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{9}=3$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(1)-3}{2*1}=\frac{-4}{2} =-2 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(1)+3}{2*1}=\frac{2}{2} =1 $

See similar equations:

| (x*x*x)+(39x)+70=0 | | 0.2=0.6(8-x) | | 3v-+12=15 | | 5x+4=22-3 | | ​(4​​9)​​y−12=(​4​​1)​​y−4 | | 5-(5x-10)=25(x-2) | | 6(-4+5x)=36 | | (X^3)+(39x)+70=0 | | 20x-2x+50+85=180 | | 3x^2=6x-1=0 | | -10x+4x-2x=-24 | | 104x2+99x-180=0 | | 28.5714=2^2t | | 140-(6x+7)=6(x+7)+x | | 6x/24=42/24 | | 6(-1/6(x-18)+1/3(x+3))=6(x+14) | | -8(x-2)=-16 | | 25x-9-15x+4=20x-6-10x+11 | | 4x/x=2=8-8/x=2 | | X+2(3+2x)=1 | | 8/5(p+1)=3/5-p | | 4x+9=5(x+3)-4 | | −3(2x-3)=−6x+9 | | -4+8x=-28 | | 4(x=-7)+12=20 | | 462x2-120x-72=0 | | 10x^2+4x-98=0 | | 4(x+5)-13=35 | | 5y+40=8y-20 | | -4n-12=-4n+12 | | x/5-1/2=3/10 | | 8x-20=-5x+2 |

Equations solver categories